Effect of Compaction and Nitrogen Placement on Yield and Nitrogen Uptake by rainfed rice, Wheat - Singh, O P; Singh, R A; Singh, Mahatim (Annals of Arid Zone, 2016)
Field experiments were conducted with three levels of soil compaction and three depths of placement of nitrogen under rainfed conditions. The compaction treatments failed to show any significant increase in the ntrogen concentration and protein percentage of rice and wheat. Nitrogen uptake by rice and wheat grains was influenced significantly due to soil compaction. Application of nitrogen by broadcasting was as good as placement of nitrogen for rice crop. However, placement of nitrogen had significant effect on wheat yield. Nitrogen content and protein percentage in grain and straw of wheat was significantly higher in deep placed nitrogen treatments as compared to broadcast application of nitrogen.